DAMPAK PEMBANGUNAN KAWASAN INDUSTRI TERPADU TERHADAP DAYA DUKUNG DAN DAYA TAMPUNG LAHAN PERMUKIMAN - Israyanti, Israyanti; Uny, Chivilya; Sriwulandari, Masfirah (STKIP PGRI Situbondo, 2024)
The development of industrial areas will impact changes in land use in their vicinity, marked by the migration of industrial workforce which affects lands designated for residential development or built-up areas. One of the integrated industrial area developments studied is the Takalar Integrated Industrial Zone. This research aims to predict the carrying capacity and accommodation capacity of residential land around the Industrial Zone in meeting the land needs due to population growth. The study uses a quantitative descriptive method with a spatial approach using Geographic Information System (GIS). The analytical techniques include overlaying thematic maps (slope inclination, soil type, rainfall, topography, land use, and disaster-prone areas) with scoring and weighting according to Minister of Public Works Regulation No. 20/PRT/M/2007 to determine land carrying capacity. Then, for land accommodation capacity, demographic data (population) is used to predict the number of residents that can be accommodated on such land. The analysis results for the carrying capacity and residential capacity for the potential area around the Industrial Zone or outside its delineation cover an area of 2.182,28 hectares, meaning 60% of this land can be developed for residential purposes, which is 1.309,37 hectares. The housing land requirement for 213.413 housing units is 1.280,48 hectares, and the requirement for public and social facilities land is 176,36 hectares. The land capacity of residential development land around the Takalar Integrated Industrial Zone for the next 10 years, by the year 2033, faces a land deficit. Therefore, policy guidance is needed for land use and allocation of residential land to other districts or to focus on vertical housing development (flats).